Ergo Care Heel Raise Exercise Is Affecting Towards Elderly Balance - Imamatul Faizah; Ratna Yunita Sari (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Elderly has decreased the ability of body functions both physically and psychologically that is physiological. Decreased body function in the elderly is caused by morphological changes in muscles and degenerative diseases, this can cause problems with balance disorders in the elderly. The purpose of this study is to explain the effect of ergo care heel raise exercise on elderly balance. This study uses a quasy experiment research design with pre-test and post-test groups. the control group with a sample of 52 respondents and the intervention group with a sample of 52 respondents. The sampling technique uses consecutive sampling. The intervention was carried out for 4 weeks (15 minutes for each intervention). This study uses the TUGT (Time up and Go Test) observation instrument. Analyze data using, Paired sample t-Test and Independent sample t-Test. The results showed that the mean decrease in TUGT scores in the intervention group 9, and in the control group 0.09. Analysis of the data obtained ergo care heel raise exercise affects the balance of the elderly in the intervention group with a value of p = 0,000 in the intervention group. Whereas in the control group the paired t-test results obtained p = 0.302. Ergo care heel raise exercise functions to control neuromuscular muscles in the joints that work to send propfferentive afferent input to the central nervous system so that it can maintain the balance of the elderly.